Using the Amphipod Hyale Nigra to Assess the Quality of Marine Sediments - Passarelli MC; Cesar A; Abessa DMS (Annals of Limnology and Oceanography - Peertechz Publications, 2017)
Few species are standardized and have been used as test organisms around the world in ecotoxicological assays. In the case of sediment assessment, there are only two amphipod species (Tiburonella viscana and Grandidierella bonnieroides) standardized protocols for toxicity test in South Atlantic region.In order to evaluate the possibility of using the epibenthic marine amphipod Hyale nigra in toxicity tests, a sensitivity test using spiked sediment method was applied, with cadmium chloride as a reference toxicant (CdCl2). Tests with environmental samples were performed to validate the test organisms. The samples were taken from Santos Estuary and Bay in state of Sao Paulo, Brazil. The historical toxicity and contamination are mentioned in the literature. The results obtained in the spiked sediment tests showed little variation in the sensitivity of Hyale nigra amphipod with a mean LC50 value of 5.73 mg.L-1 (1.51 mg.L-1 - 8.75 mg.L-1). In the tests with environmental samples, the results obtained were similar to those found in the literature regarding this sampling area. This study demonstrates the potential of Hyale nigra amphipod as a test organism in toxicity tests, once that the specie is sensitive and its results were similar to those reported in the literature on other species of amphipods that are already used in ecotoxicological studies.